Alternative Investments - Opportunities and Challenges to Capital Pension Funds - Daneva, Ivanka (Research Papers, 2020)
The paper examines contemporary aspects of investments in alternative investments in the portfolio of capital funded pension funds. They characterize the benefits of alternative investments and outline possible forms of investment in infrastructure projects. Emphasis is placed on the specifics of risks in infrastructure investments and their classification. There is a place for the regulations and practices of the pension funds to invest in alternative assets, incl. in infrastructure projects through a range of classes of financial instruments. The review of the legislation in force in our country outlines guidelines for changes in the investment restrictions on the introduction of portfolios with different risk profiles for pension funds while simultaneously creating suitable domestic financial instruments for investment in infrastructure projects.
Keywords: Capital pension insurance; Alternative investments; Infrastructure projects; Pension funds; Risks